FACTORS INFLUENCING THE CAREER INTEREST OF UDAYANA UNIVERSITY ACCOUNTING STUDENTS TOWARDS THE PUBLIC ACCOUNTING PROFESSION - I Kadek Deo Narendra Adnya Putra; Gusti Ayu Putu Eka Dewi Prihantari (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Career interest refers to an internal psychological tendency marked by feelings of attraction, enjoyment, and sustained attention toward a specific occupation without external pressure. One such interest among undergraduate accounting students is pursuing a career as a public accountant, which demands strong academic preparation, professional competence, and long-term commitment through advanced education and certification. This study aims to examine the effects of adversity intelligence, career motivation, economic motivation, professional recognition, and work environment on students’ interest in becoming public accountants at Udayana University. A quantitative approach was employed using a survey method, with data collected through questionnaires distributed to active accounting students from the Class of 2022 and alumni from the Classes of 2020 and 2021. The sample consisted of 168 respondents selected through purposive sampling. Data were analyzed using multiple linear regression, supported by classical assumption tests, model feasibility (F-test), coefficient of determination (R²), and hypothesis testing (t-test) with SPSS software. The findings reveal that adversity intelligence, economic motivation, and work environment positively influence career interest, while career motivation and professional recognition show no significant effect.